2022
DOI: 10.2528/pier22050401
|View full text |Cite
|
Sign up to set email alerts
|

Bessel Beam Generated by the Zero-Index Metalens

Abstract: Bessel beam is an important propagation-invariant optical field. The size and shape of its central spot remain unchanged in the long-distance transmission process, which has a wide application prospect. In this paper, we find that zero-index media (ZIM) metalen can be designed to realize the unique Bessel beam. On the one hand, based on the metal-dielectric multilayered structure with subwavelength unit cells, the anisotropic epsilon-near-zero media (ENZ) metalen is proposed for generating the robust Bessel be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…[17] Concerning this practical problem, a thermal zero-index cloak composed of strong circulating fluid has been designed by demonstrating an exact equivalence between a zero index (n → 0) in photonics and an infinite thermal conductivity (κ → ∞) in heat transfer (Figure 3b). [61,62] In this device, the thermal property is insensitive to details of the fluid fields, so it requires no accurate adjustment of the flow field. While the traditional bilayer cloak with low conductivity inner layer enables uniform temperature distribution inside the cloak, this zero-index cloak can track ambient temperature changes from inside as quickly as the bare object (Figure 3c).…”
Section: Enhancing Heat Transfermentioning
confidence: 99%
“…[17] Concerning this practical problem, a thermal zero-index cloak composed of strong circulating fluid has been designed by demonstrating an exact equivalence between a zero index (n → 0) in photonics and an infinite thermal conductivity (κ → ∞) in heat transfer (Figure 3b). [61,62] In this device, the thermal property is insensitive to details of the fluid fields, so it requires no accurate adjustment of the flow field. While the traditional bilayer cloak with low conductivity inner layer enables uniform temperature distribution inside the cloak, this zero-index cloak can track ambient temperature changes from inside as quickly as the bare object (Figure 3c).…”
Section: Enhancing Heat Transfermentioning
confidence: 99%
“…Such reconstruction of the nonlinear emission from nanoscale antennas represents the first step toward the application of all-dielectric nanostructures for nonlinear holography. In addition, phase-only metasurfaces are also widely used in metalens [ 32 , 34 ], which can replace traditional refractive lenses to improve the compactness and efficiency of holographic imaging systems. In 2018, Chen et al [ 50 ] showed that, by judicious design of nanofins on a surface, it is possible to simultaneously control the phase, group delay, and group delay dispersion of light, thereby achieving a transmissive achromatic metalens with a large bandwidth.…”
Section: Single Metasurface Holographymentioning
confidence: 99%
“…In comparison to digital light-field modulators and metamaterials, metasurfaces not only have the powerful ability to modulate optical properties on the subwavelength scale but also offers advantages such as low absorption loss, ultra-thinness, and small pixel size. Metasurfaces provide a new perspective for the design of various optical devices, such as orbital angular momentum devices [ 20 , 21 , 22 , 23 , 24 ], cloak devices [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and ultra-thin planar lenses [ 32 , 33 , 34 ] and spectroscopes [ 35 , 36 ]. A cutting-edge application of nanotechnology is the combination of metasurface and CGH, which composes metasurfaces by mapping CGH-generated holograms based on the local scattering properties of predesigned nanostructures to realize holography.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental demonstration has been reported in the near infrared with degenerated semiconductors such as tin-doped indium oxide (ITO) [16] and aluminum-doped zinc oxide (AZO) [20] and in the visible range. [21][22][23] Recent works have demonstrated remarkable applications of near-zero-index media such as optical edge detection, [24] Bessel beam generation, [25] low-loss, geometry-invariant optical waveguides, [26] and nonlinear alloptical modulator. [27] Here we provide a proof of concept that can be applied in the whole mid-IR spectra.…”
Section: Introductionmentioning
confidence: 99%